When Less Is More: EBUS-TBNA for the Diagnosis of Pleural Lesions. Issue 5 (October 2019) - Donghi, Stefano Maria; Prisciandaro, Elena; Sedda, Giulia; Guarize, Juliana; Spaggiari, Lorenzo
Abstract : The investigation of pleural lesions is challenging. Thoracoscopic pleural biopsies are often the chosen approach for diagnosis and, in case of malignancy, for disease staging and palliation pleurodesis. Minimally invasive techniques represent a valid option in patients that cannot undergo surgery, minimizing the risks related to more aggressive procedures. Here we report the case of a 63-year-old man with computed tomography evidence of paratracheal pleural thickening that was successfully sampled with endobronchial ultrasound-guided transbronchial needle aspiration. This technique should be considered for the diagnosis of pleural lesions adjacent to the main airway; it represents a safer, better tolerated, and less invasive alternative to operation.